Sistem Informasi Penjualan Online Spare Part dan Booking Service Motor pada Bengkel Astro Custom Depok berbasis Web - Paltrow Artahsasta Talanila; Dimpo Sinaga; Yoke Lucia Renica Rehatalanit; Muryan Awaludin (Fakultas Ilmu Komputer & Desain, 2026)
This research aims to design a web-based agate sales information system for Dwi Mulia Gems Store in Jakarta Gems Mall Rawa Bening, which faces offline marketing constraints and fierce competition. The system developed using the PHPprogramming language and MySQL database aims to increase marketing reach and product information accuracy. This research method uses a descriptive qualitative approach with a waterfall model, including the stages of planning, analysis, design, implementation, and maintenance. The results showed that the current manual system does not utilize technology. With a webbased information system, it is expected to facilitate data processing, transaction reporting, and improve store performance.